Interface buffer reinforcing structure and forming method of light high-strength ceramic-aluminum decorative composite board
Patent Information
- Application Number
- CN202611126718.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-27
AI Technical Summary
现有的陶铝复合板采用整体胶粘和机械卡扣方式实现陶瓷面层与铝合金基板的连接,但胶粘界面在湿热老化和温度交变作用下易发生界面脱粘失效,机械卡扣则存在连接点应力集中和振动松动的问题,且两种方式均无法有效缓冲陶瓷与铝合金因热膨胀系数差异引起的界面热应力;而采用整体高温冶金连接虽能提升界面结合强度,但大面积连续陶瓷层与铝合金基体之间的高刚度连接会造成冷却过程中巨大的残余应力,导致陶瓷层开裂或板件翘曲变形
1:本发明通过模块化陶瓷锚固单元的离散阵列设计,将传统整体陶瓷板分解为多个独立锚固单元,利用燕尾形锚固柱与阶梯形燕尾环形微槽形成的宏观榫卯互锁与微观环槽填充结构,系统性地解决了xianyou 陶铝复合板界面热失配应力集中和层间剥离的关键难题,同时利用低温活性钎焊连接在每个锚固柱根部与装配孔孔口环状间隙处形成冶金结合,钎料在毛细作用下填充环槽并形成致密界面层,实现了陶瓷面层与铝合金基底的高可靠连接,赋予复合板可设计性和局部损伤可修复性;
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite panel technology, specifically to an interface buffering and reinforcement structure and molding method for a lightweight, high-strength ceramic-aluminum decorative composite panel. Background Technology
[0002] Ceramic-aluminum alloy decorative composite panels combine the wear-resistance, corrosion resistance, and decorative properties of the ceramic surface with the lightweight and high-strength characteristics of the aluminum alloy substrate, making them a high-end finishing material for building curtain walls, rail transit, and interior decoration. Existing ceramic-aluminum composite panels use integral adhesive bonding and mechanical snap-fit methods to connect the ceramic surface to the aluminum alloy substrate. However, adhesive bonding is prone to interface debonding failure under humid heat aging and temperature alternation. Mechanical snap-fit methods suffer from stress concentration at connection points and vibration loosening. Furthermore, neither method effectively buffers the interfacial thermal stress caused by the difference in thermal expansion coefficients between the ceramic and aluminum alloy. While integral high-temperature metallurgical bonding can improve interfacial bonding strength, the high-rigidity connection between the large-area continuous ceramic layer and the aluminum alloy substrate creates significant residual stress during cooling, leading to cracking of the ceramic layer or warping deformation of the panel.
[0003] Existing methods for mitigating interfacial stress in ceramic-aluminum composite panels primarily rely on introducing an intermediate soft adhesive layer and reducing the thickness of the ceramic layer. While the soft adhesive layer can absorb some thermal deformation, its weather resistance and anti-aging properties are insufficient. A thin ceramic layer, on the other hand, sacrifices surface wear resistance and impact resistance. Therefore, there is an urgent need to develop a novel ceramic-aluminum decorative composite panel and its molding method that achieves synergistic optimization of stress buffering and highly reliable connections at the interfacial structural design level. This will meet the comprehensive demands of the high-end decoration market for lightweight, high-strength, long-term reliability, and designability.
[0004] To address the above problems, the present invention provides a solution. Summary of the Invention
[0005] The purpose of this invention is to provide an interface buffering and reinforcement structure and molding method for a lightweight and high-strength ceramic-aluminum decorative composite panel, which can achieve the integration of lightweight and high strength, thermal stress buffering and highly reliable interface connection of the panel, while giving the panel designability and repairability. To achieve the above objectives, the present invention adopts the following technical solution: a molding method for an interface buffer reinforcement structure of a lightweight high-strength ceramic-aluminum decorative composite panel, based on a modular ceramic anchoring unit, through the synergistic effect of discrete array assembly, low-temperature active brazing connection, flexible structural stress buffering and functional gradient interface reinforcement, to achieve the integration of macroscopic tenon and mortise interlocking, microscopic annular groove filling and controllable interface reaction wetting, thereby obtaining a lightweight high-strength ceramic-aluminum decorative composite panel with an interface buffer reinforcement structure; Furthermore, the modular ceramic anchoring unit is composed of the following components by weight percentage: 82.5% alumina powder, 5% yttrium-stabilized zirconia powder, 3.5% polyvinyl butyral, 2% dibutyl phthalate, 1.5% stearic acid, 1.2% magnesium oxide, 0.8% titanium dioxide, 0.5% oleic acid, 0.5% polyethylene glycol 400, 0.3% nano-graphite powder, 0.2% silicon carbide whiskers, 0.5% low-melting-point glass powder, and 1.5% anhydrous ethanol; Furthermore, the method for preparing the modular ceramic anchoring unit includes the following steps: A1: Place alumina powder in a vacuum drying oven, set the temperature to 120-140℃, and the vacuum degree to -0.08 to -0.10MPa, and dry for 12-16 hours to obtain dried alumina powder. Place yttrium-stabilized zirconia powder in a vacuum drying oven, set the temperature to 100-120℃, and the vacuum degree to -0.08 to -0.10MPa, and dry for 10-14 hours to obtain dried yttrium-stabilized zirconia powder. Place magnesium oxide, titanium dioxide, and silicon carbide whiskers in vacuum drying ovens, set the temperature to 100-120℃, and the vacuum degree to -0.08 to -0.10MPa, and dry for 8-12 hours to obtain dried magnesium oxide, dried titanium dioxide, and dried silicon carbide whiskers. A2: Add dry alumina powder, dry yttrium-stabilized zirconium oxide powder, dry magnesium oxide, dry titanium dioxide, dry silicon carbide whiskers and stearic acid into a ball mill, use anhydrous ethanol as the ball milling medium, set the ball milling speed to 300-400 rpm, the ball milling time to 4-6 h, and the ball-to-material ratio to 3:1. After ball milling, transfer the powder to an oven and dry it at 80-100℃ for 6-8 h. Then pass it through a 200-mesh sieve to obtain the pretreated ceramic mixed powder. A3: Place polyvinyl butyral in a vacuum drying oven, set the temperature to 60-80℃, and the vacuum degree to -0.08 to -0.10MPa, and dry for 6-10 hours to obtain dried polyvinyl butyral. Place polyethylene glycol 400 in a vacuum drying oven, set the temperature to 80-100℃, and the vacuum degree to -0.08 to -0.10MPa, and dry for 4-8 hours to obtain dried polyethylene glycol 400. A4: Add the pretreated ceramic mixed powder, dried polyvinyl butyral, dibutyl phthalate, oleic acid, dried polyethylene glycol 400, nano-graphite powder and low melting point glass powder to a mixer for mixing. Set the mixing temperature to 150-170℃, the mixing speed to 30-50 rpm, and the mixing time to 30-60 min. After mixing, crush the material and pass it through a 10-mesh sieve to obtain the injection molding feed. A5: Add the injection molding feedstock into the injection molding machine, set the injection temperature to 160-180℃, the injection pressure to 80-100MPa, and the injection speed to 15-25cm.3 / s, holding pressure is 60-80MPa, holding time is 5-10s, mold temperature is 40-60℃, injection molding yields a ceramic blank with a decorative surface on the upper surface and an integrally formed dovetail-shaped anchor column in the center of the lower surface. The anchor column body is engraved with 3 stepped dovetail annular microgrooves, and the cross-sectional dimension of the cantilever end of the anchor column is larger than the cross-sectional dimension of the root. A6: Place the ceramic green body in a degreasing furnace and heat it from room temperature to 300-350℃ at a heating rate of 0.5-1℃ / min. Hold it at 300-350℃ for 2-3 hours for low-temperature degreasing. Then heat it to 550-600℃ at a heating rate of 1.5-2.5℃ / min and hold it at 550-600℃ for 3-5 hours for medium-temperature degreasing. Flowing nitrogen gas is introduced throughout the degreasing process at a flow rate of 2-4L / min. After degreasing, a degreased ceramic green body is obtained. A7: The degreased ceramic green body is fed into a high-temperature sintering furnace and heated to 1100-1300℃ at a heating rate of 3-6℃ / min. It is then held at 1100-1300℃ for 1-2 hours for pre-sintering. Next, it is heated to 1620-1680℃ at a heating rate of 5-10℃ / min and held at 1620-1680℃ for 2-4 hours for densification sintering. Flowing argon gas is introduced throughout the sintering process at a flow rate of 1-3L / min. After sintering, it is cooled to 800℃ at a cooling rate of 5-10℃ / min and held at 800℃ for 1-2 hours. After holding, it is cooled to room temperature with the furnace. Then, the anchor column part of the ceramic anchoring unit is precision ground. After grinding, the dimensional tolerance of the anchor column is controlled within ±0.015mm, and the surface roughness Ra≤0.8um, thus obtaining the modular ceramic anchoring unit. Furthermore, the alumina powder has an average particle size of 0.8 μm, and the magnesium oxide has an average particle size of 0.2 μm; the yttrium-stabilized zirconium oxide powder has a yttrium content of 3% and an average particle size of 0.5 μm; the silicon carbide whiskers have a diameter of 0.8 μm, a length of 20 μm, and an aspect ratio of 25; the low-melting-point glass powder is bismuth borosilicate glass powder with a softening point of 485°C and an average particle size of 0.8 μm. Furthermore, a method for forming an interface buffer reinforcement structure of a lightweight, high-strength ceramic-aluminum decorative composite panel includes the following steps: S1: Select 6061 aluminum alloy powder, with a feeding amount of 8-15 kg. Place the aluminum alloy powder in a vacuum drying oven, set the temperature to 100-120℃, the vacuum degree to -0.06 to -0.08 MPa, and the drying time to 8-12 h to obtain dried aluminum alloy powder. Load the dried aluminum alloy powder into the powder supply cylinder of the selective laser melting equipment. Import the three-dimensional model of the aluminum alloy lattice substrate into the control system of the equipment, set the laser power to 200-300W, the scanning speed to 800-1200 mm / s, the powder layer thickness to 30-50 μm, the spot diameter to 60-100 μm, the scanning spacing to 80-120 μm, the substrate preheating temperature to 150-200℃, and the oxygen content in the cavity to below 100 ppm. Use a strip scanning strategy to melt and form the aluminum alloy lattice substrate layer by layer. S2: The aluminum alloy lattice substrate is separated from the substrate by wire cutting and placed in a vacuum heat treatment furnace for stress-relief annealing. The annealing temperature is set at 280-320℃ and the annealing holding time is 2-4h. After annealing, the substrate is cooled to below 100℃ in the furnace and then air-cooled to room temperature to obtain the stress-relief aluminum alloy lattice substrate. The stress-relief aluminum alloy lattice substrate is then subjected to solution aging heat treatment. The solution temperature is set at 520-540℃ and the solution holding time is 1-2h. After solution treatment, the substrate is immediately water-quenched at a water temperature of 25-35℃. After water quenching, the substrate is transferred to an aging furnace. The aging temperature is set at 155-175℃ and the aging holding time is 6-10h. After aging, the substrate is air-cooled to room temperature to obtain the heat-treated aluminum alloy lattice substrate. S3: Arrange the modular ceramic anchoring units according to the designed array and insert them one by one into the corresponding holes of the aluminum alloy lattice substrate. The number of ceramic anchoring units inserted is 200-280 per square meter. Use assembly positioning fixtures to ensure that the upper surfaces of each ceramic unit are coplanar and that the dovetail anchoring posts are completely suspended inside the aluminum alloy lattice substrate. The cantilever gap between the end face of the anchoring post and the bottom surface of the assembly hole of the lattice substrate is 1-2mm, resulting in a pre-assembled ceramic surface lattice substrate. After assembly, place the ceramic surface lattice substrate... The pre-assembled assembly is placed on the inspection table and inspected under an inspection light source with an illuminance of 1200 lx to check the neatness of the ceramic unit arrangement and the insertion depth of the anchor column. It is confirmed that there are no misalignments or missing insertion defects. The ceramic surface lattice substrate pre-assembled assembly is placed in a preheating furnace and preheated as a whole in an air atmosphere or protective atmosphere. The preheating temperature is set to 380-420℃, the heating rate is 3-6℃ / min, and the holding time is 20-40min to make the overall temperature of the pre-assembled assembly uniform, thus obtaining the preheated pre-assembled assembly. S4: Transfer the preheated pre-assembled body to the connecting fixture, which has a heat preservation function and a fixture temperature of 380-420℃. Apply a quantitative amount of active brazing filler paste to the annular gap between the root of each anchor post and the opening of the assembly hole. The amount of brazing filler paste required for each ceramic anchor unit is 30-60g. Set the heating temperature of the connecting fixture to 580-610℃ to melt the active brazing filler paste. Apply an auxiliary pressure of 0.1-0.3MPa and hold at 580-610℃ for 5-10 minutes to complete the interface connection. S5: After completing the interface connection, remove the composite plate from the connection fixture and immediately transfer it into a homogenizing furnace. Hold it at 550-580℃ for 1-2 hours to release high-temperature stress. Then, cool it using a gradient temperature control method. Set the first cooling stage to cool from 550-580℃ to 300-320℃ at a rate of 1-2℃ / min, the second cooling stage to cool from 300-320℃ to 150-180℃ at a rate of 5-8℃ / min, and the third cooling stage to cool naturally from 150-180℃ to room temperature with the furnace. After cooling, the interface-bonded ceramic-aluminum composite plate is obtained. S6: The interface-bonded ceramic-aluminum composite panel is sent to the grinding and polishing station. Diamond grinding fluid is used to grind and polish the ceramic surface layer step by step. The coarse grinding wheel mesh size is set to 180-320 mesh, and the coarse grinding feed is 0.05-0.1mm. The semi-fine grinding wheel mesh size is set to 600-800 mesh, and the semi-fine grinding feed is 0.02-0.05mm. The fine grinding wheel mesh size is set to 1500-2000 mesh, and the fine grinding feed is 0.01-0.02mm. The polishing cloth wheel speed is 1200-1800rpm, the polishing fluid particle size is 0.5-1.5um, and the polishing time is 5-15min. After polishing, the composite panel is placed on the inspection table and the surface roughness and gloss of the ceramic surface layer are checked under an inspection light source with an illuminance of 1200lx. It is confirmed that there are no scratches or pit defects, and a lightweight, high-strength ceramic-aluminum decorative composite panel with an interface buffer reinforcement structure is obtained.
[0006] Furthermore, in the three-dimensional model of the aluminum alloy lattice substrate mentioned in step S1, a compliant buffer structure is designed at the position corresponding to the assembly hole of each ceramic anchoring unit. The compliant buffer structure consists of three spiral elastic thin-walled beams distributed in a ring around the assembly hole. The thickness of the thin-walled beam is 0.5 mm, the length is 3 mm, and the spiral angle is 90°. The active solder paste mentioned in step S4 is composed of Al-Si eutectic alloy powder, Mg powder, potassium fluoroaluminate flux, and ethyl cellulose. The Si content in the Al-Si eutectic alloy powder is 12%, and the mass ratio of Al-Si eutectic alloy powder, Mg powder, potassium fluoroaluminate flux, and ethyl cellulose is 88:2:8:2. In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows: 1. This invention decomposes the traditional integral ceramic plate into multiple independent anchoring units through the discrete array design of modular ceramic anchoring units. It systematically solves the key problems of stress concentration and interlayer delamination at the interface of ceramic-aluminum composite plates by using the macroscopic tenon-and-mortise interlocking and microscopic annular groove filling structure formed by dovetail anchoring columns and stepped dovetail annular microgrooves. At the same time, it uses low-temperature active brazing to form a metallurgical bond at the annular gap between the root of each anchoring column and the opening of the assembly hole. The brazing filler fills the annular groove under capillary action and forms a dense interface layer, realizing a highly reliable connection between the ceramic surface layer and the aluminum alloy substrate, giving the composite plate designability and repairability of local damage. 2: This invention designs a flexible buffer structure with spiral elastic thin-walled beams distributed in a ring around the assembly holes in a three-dimensional model of an aluminum alloy lattice substrate. When the composite plate undergoes thermal mismatch deformation under thermal cycling or external impact, the thin-walled beams absorb thermal stress and impact energy through elastic and plastic deformation, effectively preventing cracks from initiating at the interface and spreading to the surrounding area. This solves the problem that existing rigid connection structures cannot adapt to the interface fatigue failure caused by the difference in thermal expansion coefficients between ceramics and aluminum alloys, and significantly improves the interface durability and impact damage tolerance of the composite plate under extreme temperature alternation environment. 3: This invention utilizes a synergistic process of gradient temperature-controlled cooling and preheated brazing. By preheating the pre-assembled whole, the ceramic anchoring unit and the aluminum alloy lattice substrate reach a uniform thermal state before brazing. After brazing, a three-stage gradient cooling is used to gradually release residual stress. Combined with the stress relaxation function of the compliant buffer structure, this provides a systematic solution from structural design to molding process for the interface buffering enhancement of lightweight high-strength ceramic-aluminum decorative composite panels. Detailed Implementation
[0007] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to specific embodiments.
[0008] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0009] Example 1: 8250g of alumina powder was placed in a vacuum drying oven at 120℃ and -0.08MPa for 12 hours to obtain 8235g of dried alumina powder. 500g of yttrium-stabilized zirconia powder was placed in a vacuum drying oven at 100℃ and -0.08MPa for 10 hours to obtain 498g of dried yttrium-stabilized zirconia powder. 120g of magnesium oxide, 80g of titanium dioxide, and 20g of silicon carbide whiskers were placed in separate vacuum drying ovens at 100℃ and -0.08MPa for 8 hours to obtain 118g of dried magnesium oxide, 79g of dried titanium dioxide, and 19g of dried silicon carbide whiskers. 2: Add 8235g of dry alumina powder, 498g of dry yttrium-stabilized zirconia powder, 118g of dry magnesium oxide, 79g of dry titanium dioxide, 19g of dry silicon carbide whiskers and 150g of stearic acid to a ball mill. Use 150g of anhydrous ethanol as the ball milling medium. Set the ball milling speed to 300 rpm, the ball milling time to 4 hours, and the ball-to-material ratio to 3:1. After ball milling, transfer the powder to an oven and dry it at 80℃ for 6 hours. Pass the powder through a 200-mesh sieve to obtain 9042g of pretreated ceramic mixed powder. 3: Place 350g of polyvinyl butyral in a vacuum drying oven, set the temperature to 60℃ and the vacuum degree to -0.08MPa, and dry for 6h to obtain 345g of dried polyvinyl butyral. Place 50g of polyethylene glycol 400 in a vacuum drying oven, set the temperature to 80℃ and the vacuum degree to -0.08MPa, and dry for 4h to obtain 49g of dried polyethylene glycol 400. 4: Add 9042g of pretreated ceramic mixed powder, 345g of dried polyvinyl butyral, 200g of dibutyl phthalate, 50g of oleic acid, 49g of dried polyethylene glycol 400, 30g of nano-graphite powder and 50g of low melting point glass powder to a mixer for mixing. Set the mixing temperature to 150℃, the mixing speed to 30rpm and the mixing time to 30min. After mixing, crush the material and pass it through a 10-mesh sieve to obtain 9710g of injection molding feedstock. 5. Add 9710g of injection molding feedstock to the injection molding machine, set the injection temperature to 160℃, the injection pressure to 80MPa, and the injection speed to 15cm. 3 / s, holding pressure is 60MPa, holding time is 5s, mold temperature is 40℃, injection molding yields a ceramic blank with a decorative surface on the upper surface and an integrally formed dovetail-shaped anchor column in the center of the lower surface. The anchor column body is engraved with 3 stepped dovetail annular microgrooves, and the cross-sectional dimension of the cantilever end of the anchor column is larger than the cross-sectional dimension of the root. 6: Place the ceramic green body in a degreasing furnace and heat it from room temperature to 300℃ at a heating rate of 0.5℃ / min. Hold it at 300℃ for 2 hours for low-temperature degreasing. Then heat it to 550℃ at a heating rate of 1.5℃ / min and hold it at 550℃ for 3 hours for medium-temperature degreasing. Flowing nitrogen gas is introduced throughout the degreasing process at a flow rate of 2L / min. After degreasing, 8516g of degreased ceramic green body is obtained. 7: 8516g of degreased ceramic green body was fed into a high-temperature sintering furnace and heated to 1100℃ at a heating rate of 3℃ / min. It was held at 1100℃ for 1h for pre-sintering, and then heated to 1620℃ at a heating rate of 5℃ / min. It was held at 1620℃ for 2h for densification sintering. Flowing argon gas was introduced throughout the sintering process at a flow rate of 1L / min. After sintering, it was cooled to 800℃ at a cooling rate of 5℃ / min and held at 800℃ for 1h. After holding, it was cooled to room temperature with the furnace. Then, the anchor column part of the ceramic anchoring unit was precision ground. The dimensional tolerance of the anchor column after grinding was controlled within ±0.015mm, and the surface roughness Ra≤0.8um, resulting in 8042g of the modular ceramic anchoring unit prepared in Example 1. Example 2:1: 8250g of alumina powder was placed in a vacuum drying oven at a temperature of 140℃ and a vacuum of -0.10MPa for 16 hours to obtain 8228g of dried alumina powder. 500g of yttrium-stabilized zirconia powder was placed in a vacuum drying oven at a temperature of 120℃ and a vacuum of -0.10MPa for 14 hours to obtain 496g of dried yttrium-stabilized zirconia powder. 120g of magnesium oxide, 80g of titanium dioxide, and 20g of silicon carbide whiskers were placed in vacuum drying ovens at a temperature of 120℃ and a vacuum of -0.10MPa for 12 hours to obtain 117g of dried magnesium oxide, 78g of dried titanium dioxide, and 18g of dried silicon carbide whiskers. 2: Add 8228g of dry alumina powder, 496g of dry yttrium-stabilized zirconia powder, 117g of dry magnesium oxide, 78g of dry titanium dioxide, 18g of dry silicon carbide whiskers and 150g of stearic acid to a ball mill. Use 150g of anhydrous ethanol as the ball milling medium. Set the ball milling speed to 400 rpm, the ball milling time to 6 hours, and the ball-to-material ratio to 3:1. After ball milling, transfer the powder to an oven and dry it at 100℃ for 8 hours. Pass the powder through a 200-mesh sieve to obtain 9030g of pretreated ceramic mixed powder. 3: Place 350g of polyvinyl butyral in a vacuum drying oven, set the temperature to 80℃ and the vacuum degree to -0.10MPa, and dry for 10h to obtain 342g of dried polyvinyl butyral. Place 50g of polyethylene glycol 400 in a vacuum drying oven, set the temperature to 100℃ and the vacuum degree to -0.10MPa, and dry for 8h to obtain 48g of dried polyethylene glycol 400. 4: Add 9030g of pretreated ceramic mixed powder, 342g of dried polyvinyl butyral, 200g of dibutyl phthalate, 50g of oleic acid, 48g of dried polyethylene glycol 400, 30g of nano-graphite powder and 50g of low melting point glass powder to a mixer for mixing. Set the mixing temperature to 170℃, the mixing speed to 50rpm, and the mixing time to 60min. After mixing, crush the material and pass it through a 10-mesh sieve to obtain 9692g of injection molding feedstock. 5. Add 9692g of injection molding feedstock to the injection molding machine, set the injection temperature to 180℃, the injection pressure to 100MPa, and the injection speed to 25cm. 3 / s, holding pressure is 80MPa, holding time is 10s, mold temperature is 60℃, injection molding yields a ceramic blank with a decorative surface on the upper surface and an integrally formed dovetail-shaped anchor column in the center of the lower surface. The anchor column body is engraved with 3 stepped dovetail annular microgrooves, and the cross-sectional dimension of the cantilever end of the anchor column is larger than the cross-sectional dimension of the root. 6: Place the ceramic green body in a degreasing furnace and heat it from room temperature to 350℃ at a heating rate of 1℃ / min. Hold it at 350℃ for 3 hours for low-temperature degreasing. Then heat it to 600℃ at a heating rate of 2.5℃ / min and hold it at 600℃ for 5 hours for medium-temperature degreasing. Flowing nitrogen gas is introduced throughout the degreasing process at a flow rate of 4L / min. After degreasing, 8468g of degreased ceramic green body is obtained. 7: 8468g of degreased ceramic green body was fed into a high-temperature sintering furnace and heated to 1300℃ at a heating rate of 6℃ / min. It was held at 1300℃ for 2h for pre-sintering, and then heated to 1680℃ at a heating rate of 10℃ / min. It was held at 1680℃ for 4h for densification sintering. Flowing argon gas was introduced throughout the sintering process at a flow rate of 3L / min. After sintering, it was cooled to 800℃ at a cooling rate of 10℃ / min and held at 800℃ for 2h. After holding, it was cooled to room temperature with the furnace. Then, the anchor column part of the ceramic anchoring unit was precision ground. The dimensional tolerance of the anchor column after grinding was controlled within ±0.015mm, and the surface roughness Ra≤0.8um, resulting in 7986g of the modular ceramic anchoring unit prepared in Example 2. Example 3:1: 6061 aluminum alloy powder was selected, and the amount of aluminum alloy powder fed was 8kg. The aluminum alloy powder was placed in a vacuum drying oven, and the temperature was set to 100℃, the vacuum degree to -0.06MPa, and the drying time to 8h to obtain dried aluminum alloy powder. The dried aluminum alloy powder was loaded into the powder supply cylinder of the selective laser melting equipment. The three-dimensional model of the aluminum alloy lattice substrate was imported into the control system of the equipment. The laser power was set to 200W, the scanning speed to 800mm / s, the powder layer thickness to 30um, the spot diameter to 60um, the scanning interval to 80um, the substrate preheating temperature to 150℃, and the oxygen content in the cavity to be controlled below 100ppm. The aluminum alloy lattice substrate was obtained by melting and forming layer by layer using a strip scanning strategy. 2: The aluminum alloy lattice substrate is separated from the substrate by wire cutting and placed in a vacuum heat treatment furnace for stress-relief annealing. The annealing temperature is set at 280℃ and the annealing holding time is 2h. After annealing, the substrate is cooled to below 100℃ in the furnace and then air-cooled to room temperature to obtain the stress-relief aluminum alloy lattice substrate. The stress-relief aluminum alloy lattice substrate is then subjected to solution aging heat treatment. The solution temperature is set at 520℃ and the solution holding time is 1h. After solution treatment, the substrate is immediately water-quenched at 25℃. After water quenching, the substrate is transferred to an aging furnace. The aging temperature is set at 155℃ and the aging holding time is 6h. After aging, the substrate is air-cooled to room temperature to obtain the heat-treated aluminum alloy lattice substrate. 3: The modular ceramic anchoring units prepared in Example 1 are arranged in the designed array and inserted one by one into the corresponding holes of the aluminum alloy lattice substrate. The number of ceramic anchoring units inserted is 200 per square meter. The assembly positioning fixture is used to ensure that the upper surface of each ceramic unit is coplanar and that the dovetail anchoring column is completely suspended inside the aluminum alloy lattice substrate. The cantilever gap between the end face of the anchoring column and the bottom surface of the assembly hole of the lattice substrate is 1 mm, thus obtaining a pre-assembled ceramic surface lattice substrate. After assembly, the pre-assembled ceramic surface lattice substrate is placed on the inspection table. Under the inspection light source with an illuminance of 1200 lx, the neatness of the ceramic unit arrangement and the insertion depth of the anchoring column are checked to confirm that there is no misalignment or insertion defects. The pre-assembled ceramic surface lattice substrate is placed in a preheating furnace and preheated as a whole in an air atmosphere or protective atmosphere. The preheating temperature is set to 380℃, the heating rate is 3℃ / min, and the holding time is 20min to make the overall temperature of the pre-assembled body uniform, thus obtaining a preheated pre-assembled body. 4. Transfer the preheated pre-assembled parts to the connecting fixture, which has a heat preservation function and a fixture temperature of 380℃. Apply a measured amount of active brazing filler paste to the annular gap between the root of each anchor post and the opening of the assembly hole. The amount of brazing filler paste required for each ceramic anchor unit is 30g. Set the heating temperature of the connecting fixture to 580℃ to melt the active brazing filler paste. Apply an auxiliary pressure of 0.1MPa and hold at 580℃ for 5 minutes to complete the interface connection. 5. After completing the interface connection, remove the composite plate from the connection fixture and immediately transfer it into the uniform temperature furnace. Hold it at 550℃ for 1 hour to release high-temperature stress. Then, cool it using a gradient temperature control method. Set the first cooling stage to cool from 550℃ to 300℃ at a rate of 1℃ / min, the second cooling stage to cool from 300℃ to 150℃ at a rate of 5℃ / min, and the third cooling stage to cool naturally from 150℃ to room temperature with the furnace. After cooling, the interface-bonded ceramic-aluminum composite plate is obtained. 6. The interface-bonded ceramic-aluminum composite panel is sent to the grinding and polishing station. Diamond grinding fluid is used to grind and polish the ceramic surface layer step by step. The coarse grinding wheel is set with a mesh size of 180 and a feed rate of 0.05 mm. The semi-fine grinding wheel is set with a mesh size of 600 and a feed rate of 0.02 mm. The fine grinding wheel is set with a mesh size of 1500 and a feed rate of 0.01 mm. The polishing cloth wheel speed is 1200 rpm, the polishing fluid particle size is 0.5 μm, and the polishing time is 5 min. After polishing, the composite panel is placed on the inspection table and the surface roughness and gloss of the ceramic surface layer are checked under an inspection light source with an illuminance of 1200 lx. It is confirmed that there are no scratches or pit defects, and the lightweight high-strength ceramic-aluminum decorative composite panel with an interface buffer reinforcement structure prepared in Example 3 is obtained.
[0010] Example 4:1: 6061 aluminum alloy powder was selected, and the amount of aluminum alloy powder fed was 15kg. The aluminum alloy powder was placed in a vacuum drying oven, and the temperature was set to 120℃, the vacuum degree to -0.08MPa, and the drying time to 12h to obtain dried aluminum alloy powder. The dried aluminum alloy powder was loaded into the powder supply cylinder of the selective laser melting equipment. The three-dimensional model of the aluminum alloy lattice substrate was imported into the control system of the equipment. The laser power was set to 300W, the scanning speed to 1200mm / s, the powder layer thickness to 50um, the spot diameter to 100um, the scanning interval to 120um, the substrate preheating temperature to 200℃, and the oxygen content in the cavity to be controlled below 100ppm. The aluminum alloy lattice substrate was obtained by melting and forming layer by layer using a strip scanning strategy. 2: The aluminum alloy lattice substrate is separated from the substrate by wire cutting and placed in a vacuum heat treatment furnace for stress-relief annealing. The annealing temperature is set at 320℃ and the annealing holding time is 4h. After annealing, the substrate is cooled to below 100℃ in the furnace and then air-cooled to room temperature to obtain the stress-relief aluminum alloy lattice substrate. The stress-relief aluminum alloy lattice substrate is then subjected to solution aging heat treatment. The solution temperature is set at 540℃ and the solution holding time is 2h. After solution treatment, the substrate is immediately water-quenched at 35℃. After water quenching, the substrate is transferred to an aging furnace. The aging temperature is set at 175℃ and the aging holding time is 10h. After aging, the substrate is air-cooled to room temperature to obtain the heat-treated aluminum alloy lattice substrate. 3: The modular ceramic anchoring units prepared in Example 2 are arranged in the designed array and inserted one by one into the corresponding holes of the aluminum alloy lattice substrate. The number of ceramic anchoring units inserted is 280 per square meter. The assembly positioning fixture is used to ensure that the upper surface of each ceramic unit is coplanar and that the dovetail anchoring column is completely suspended inside the aluminum alloy lattice substrate. The cantilever gap between the end face of the anchoring column and the bottom surface of the assembly hole of the lattice substrate is 2 mm, thus obtaining a pre-assembled ceramic surface lattice substrate. After assembly, the pre-assembled ceramic surface lattice substrate is placed on the inspection table and the neatness of the ceramic unit arrangement and the insertion depth of the anchoring column are checked under an inspection light source with an illuminance of 1200 lx. It is confirmed that there is no misalignment or insertion defect. The pre-assembled ceramic surface lattice substrate is placed in a preheating furnace and preheated as a whole in an air atmosphere or protective atmosphere. The preheating temperature is set to 420℃, the heating rate is 6℃ / min, and the holding time is 40min, so that the overall temperature of the pre-assembled body is uniform, thus obtaining a preheated pre-assembled body. 4. Transfer the preheated pre-assembled parts to the connecting fixture, which has a heat preservation function and a fixture temperature of 420℃. Apply a measured amount of active brazing filler paste to the annular gap between the root of each anchor post and the opening of the assembly hole. The amount of brazing filler paste required for each ceramic anchor unit is 60g. Set the heating temperature of the connecting fixture to 610℃ to melt the active brazing filler paste. Apply an auxiliary pressure of 0.3MPa and hold at 610℃ for 10 minutes to complete the interface connection. 5. After completing the interface connection, remove the composite plate from the connection fixture and immediately transfer it into a uniform furnace. Hold it at 580℃ for 2 hours to release high-temperature stress. Then, cool it using a gradient temperature control method. Set the first cooling stage to cool from 580℃ to 320℃ at a rate of 2℃ / min, the second cooling stage to cool from 320℃ to 180℃ at a rate of 8℃ / min, and the third cooling stage to cool naturally from 180℃ to room temperature with the furnace. After cooling, the interface-bonded ceramic-aluminum composite plate is obtained. 6. The interface-bonded ceramic-aluminum composite panel is sent to the grinding and polishing station. Diamond grinding fluid is used to grind and polish the ceramic surface layer step by step. The coarse grinding wheel is set with a mesh size of 320 and a feed rate of 0.1 mm. The semi-fine grinding wheel is set with a mesh size of 800 and a feed rate of 0.05 mm. The fine grinding wheel is set with a mesh size of 2000 and a feed rate of 0.02 mm. The polishing cloth wheel speed is 1800 rpm, the polishing fluid particle size is 1.5 μm, and the polishing time is 15 min. After polishing, the composite panel is placed on the inspection table and the surface roughness and gloss of the ceramic surface layer are checked under an inspection light source with an illuminance of 1200 lx. It is confirmed that there are no scratches or pit defects, and the lightweight high-strength ceramic-aluminum decorative composite panel with an interface buffer reinforcement structure prepared in Example 4 is obtained.
[0011] Comparative Example 1: The difference between this comparative example and Example 3 is that the modular ceramic anchoring unit prepared in Example 1 is replaced with a whole piece of alumina ceramic plate of equal area, and the back of the ceramic plate has a planar structure, while the other components and processes remain unchanged. The specific preparation method is as follows: 1. Select 6061 aluminum alloy powder, with a feeding amount of 8kg. Place the aluminum alloy powder in a vacuum drying oven, set the temperature to 100℃, the vacuum degree to -0.06MPa, and the drying time to 8h to obtain dried aluminum alloy powder. Load the dried aluminum alloy powder into the powder supply cylinder of the selective laser melting equipment. Import the three-dimensional model of the aluminum alloy lattice substrate into the control system of the equipment. Set the laser power to 200W, the scanning speed to 800mm / s, the powder layer thickness to 30um, the spot diameter to 60um, the scanning interval to 80um, the substrate preheating temperature to 150℃, and the oxygen content in the cavity to below 100ppm. Use a strip scanning strategy to melt and form the aluminum alloy lattice substrate layer by layer. 2: The aluminum alloy lattice substrate is separated from the substrate by wire cutting and placed in a vacuum heat treatment furnace for stress-relief annealing. The annealing temperature is set at 280℃ and the annealing holding time is 2h. After annealing, the substrate is cooled to below 100℃ in the furnace and then air-cooled to room temperature to obtain the stress-relief aluminum alloy lattice substrate. The stress-relief aluminum alloy lattice substrate is then subjected to solution aging heat treatment. The solution temperature is set at 520℃ and the solution holding time is 1h. After solution treatment, the substrate is immediately water-quenched at 25℃. After water quenching, the substrate is transferred to an aging furnace. The aging temperature is set at 155℃ and the aging holding time is 6h. After aging, the substrate is air-cooled to room temperature to obtain the heat-treated aluminum alloy lattice substrate. 3: The back of the alumina ceramic plate is bonded to the surface of the aluminum alloy lattice substrate to obtain a ceramic surface lattice substrate pre-assembly. After assembly, the ceramic surface lattice substrate pre-assembly is placed on an inspection table and the bonding condition between the ceramic plate and the lattice substrate is checked under an inspection light source with an illuminance of 1200 lx to confirm that there are no misalignment defects. The ceramic surface lattice substrate pre-assembly is then placed in a preheating furnace and preheated in an air atmosphere. The preheating temperature is set to 380℃, the heating rate is 3℃ / min, and the holding time is 20min to ensure that the overall temperature of the pre-assembly is uniform, thus obtaining a preheated pre-assembly. 4. Transfer the preheated pre-assembled body to the connecting fixture, which has a heat preservation function and a fixture temperature of 380℃. Apply a quantitative amount of active solder paste to the periphery and central area of the contact surface between the ceramic plate and the lattice substrate. The total amount of solder paste required is 6000g. Set the heating temperature of the connecting fixture to 580℃ to melt the active solder. Apply an auxiliary pressure of 0.1MPa and hold at 580℃ for 5 minutes to complete the interface connection. 5. After completing the interface connection, remove the composite plate from the connection fixture and immediately transfer it into the uniform temperature furnace. Hold it at 550℃ for 1 hour to release high-temperature stress. Then, cool it using a gradient temperature control method. Set the first cooling stage to cool from 550℃ to 300℃ at a rate of 1℃ / min, the second cooling stage to cool from 300℃ to 150℃ at a rate of 5℃ / min, and the third cooling stage to cool naturally from 150℃ to room temperature with the furnace. After cooling, the interface-bonded ceramic-aluminum composite plate is obtained. 6. The interface-bonded ceramic-aluminum composite panel was sent to the grinding and polishing station. Diamond grinding fluid was used to grind and polish the ceramic surface layer step by step. The coarse grinding wheel was set with a mesh size of 180 and a feed rate of 0.05 mm. The semi-fine grinding wheel was set with a mesh size of 600 and a feed rate of 0.02 mm. The fine grinding wheel was set with a mesh size of 1500 and a feed rate of 0.01 mm. The polishing cloth wheel speed was 1200 rpm. The polishing fluid particle size was 0.5 μm. The polishing time was 5 min. After polishing, the composite panel was placed on the inspection table. The surface roughness and gloss of the ceramic surface layer were checked under an inspection light source with an illuminance of 1200 lx. It was confirmed that there were no scratches or pit defects. The ceramic-aluminum decorative composite panel prepared in Comparative Example 1 was obtained.
[0012] Comparative Example 2: The difference between this comparative example and Example 3 is that the three-dimensional model of the aluminum alloy lattice substrate does not have a compliant buffer structure designed, the assembly holes have rigid hole walls, and the other components and processes remain unchanged. The specific preparation method is as follows: 1. Select 6061 aluminum alloy powder, with a feeding amount of 8kg. Place the aluminum alloy powder in a vacuum drying oven, set the temperature to 100℃, the vacuum degree to -0.06MPa, and the drying time to 8h to obtain dried aluminum alloy powder. Load the dried aluminum alloy powder into the powder supply cylinder of the selective laser melting equipment. Import the three-dimensional model of the aluminum alloy lattice substrate without a compliant buffer structure into the control system of the equipment. Set the laser power to 200W, the scanning speed to 800mm / s, the powder layer thickness to 30um, the spot diameter to 60um, the scanning spacing to 80um, the substrate preheating temperature to 150℃, and the oxygen content in the cavity to below 100ppm. Use a strip scanning strategy to melt and form layer by layer to obtain an aluminum alloy lattice substrate without a buffer structure. 2: The unbuffered aluminum alloy lattice substrate is separated from the substrate by wire cutting and placed in a vacuum heat treatment furnace for stress-relief annealing. The annealing temperature is set at 280℃ and the annealing holding time is 2h. After annealing, it is cooled to below 100℃ in the furnace and then air-cooled to room temperature to obtain the stress-relieved unbuffered aluminum alloy lattice substrate. The stress-relieved unbuffered aluminum alloy lattice substrate is then subjected to solution aging heat treatment. The solution temperature is set at 520℃ and the solution holding time is 1h. After solution treatment, it is immediately water-quenched at 25℃. After water quenching, it is transferred to an aging furnace. The aging temperature is set at 155℃ and the aging holding time is 6h. After aging, it is air-cooled to room temperature to obtain the heat-treated unbuffered aluminum alloy lattice substrate. 3: The modular ceramic anchoring units prepared in Example 1 are arranged in the designed array and inserted one by one into the corresponding holes of the aluminum alloy lattice substrate without buffer structure. The number of ceramic anchoring units inserted is 200 per square meter. The assembly positioning fixture is used to ensure that the upper surface of each ceramic unit is coplanar and that the dovetail anchoring column is completely suspended inside the aluminum alloy lattice substrate without buffer structure. The cantilever gap between the end face of the anchoring column and the bottom surface of the assembly hole of the lattice substrate is 1 mm, thus obtaining the ceramic surface layer-lattice substrate pre-assembly. After assembly, the ceramic surface layer-lattice substrate pre-assembly is placed on the inspection table. Under the inspection light source with an illuminance of 1200 lx, the neatness of the ceramic unit arrangement and the insertion depth of the anchoring column are checked to confirm that there is no misalignment or insertion defect. The ceramic surface layer-lattice substrate pre-assembly is placed in a preheating furnace and preheated as a whole in an air atmosphere. The preheating temperature is set to 380℃, the heating rate is 3℃ / min, and the holding time is 20min to make the overall temperature of the pre-assembly uniform, thus obtaining the preheated pre-assembly. 4. Transfer the preheated pre-assembled parts to the connecting fixture, which has a heat preservation function and a fixture temperature of 380℃. Apply a measured amount of active brazing filler paste to the annular gap between the root of each anchor post and the opening of the assembly hole. The amount of brazing filler paste required for each ceramic anchor unit is 30g. Set the heating temperature of the connecting fixture to 580℃ to melt the active brazing filler paste. Apply an auxiliary pressure of 0.1MPa and hold at 580℃ for 5 minutes to complete the interface connection. 5. After completing the interface connection, remove the composite plate from the connection fixture and immediately transfer it into the uniform temperature furnace. Hold it at 550℃ for 1 hour to release high-temperature stress. Then, cool it using a gradient temperature control method. Set the first cooling stage to cool from 550℃ to 300℃ at a rate of 1℃ / min, the second cooling stage to cool from 300℃ to 150℃ at a rate of 5℃ / min, and the third cooling stage to cool naturally from 150℃ to room temperature with the furnace. After cooling, the interface-bonded ceramic-aluminum composite plate is obtained. 6: The interface-bonded ceramic-aluminum composite panel was sent to the grinding and polishing station. Diamond grinding fluid was used to grind and polish the ceramic surface layer step by step. The coarse grinding wheel was set with a mesh size of 180 and a feed rate of 0.05 mm. The semi-fine grinding wheel was set with a mesh size of 600 and a feed rate of 0.02 mm. The fine grinding wheel was set with a mesh size of 1500 and a feed rate of 0.01 mm. The polishing cloth wheel speed was 1200 rpm. The polishing fluid particle size was 0.5 μm. The polishing time was 5 min. After polishing, the composite panel was placed on the inspection table. The surface roughness and gloss of the ceramic surface layer were checked under an inspection light source with an illuminance of 1200 lx. It was confirmed that there were no scratches or pit defects. The lightweight and high-strength ceramic-aluminum decorative composite panel with an interface buffering and reinforcing structure prepared in Comparative Example 2 was obtained.
[0013] Basic physical performance testing The lightweight, high-strength ceramic-aluminum decorative composite panels prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2 were cut into 300mm × 300mm samples. After being placed under standard conditions for 24 hours, the tensile strength of the composite panels was tested according to GB / T 228.1-2010 "Metallic materials - Tensile testing - Part 1: Test method at room temperature", the flexural strength was tested according to GB / T 1447-2005 "Fiber reinforced plastics - Tensile properties test method", the interfacial peel strength between the ceramic surface layer and the aluminum alloy substrate was tested according to GB / T 7122-1996 "Determination of peel strength of high-strength adhesives - Floating roller method", and the density was tested according to GB / T 1463-2005 "Determination of density and relative density of fiber reinforced plastics". The brazing filler morphology at the interface between the ceramic anchor post and the aluminum alloy lattice substrate was observed using a scanning electron microscope. Each group of samples was tested in parallel three times, and the average value was recorded. Table 1. Results of Basic Physical Performance Tests density <![CDATA[2.65g / cm 3 ]]> <![CDATA[2.72g / cm 3 ]]> <![CDATA[2.85g / cm 3 ]]> <![CDATA[2.64g / cm 3 ]]> Tensile strength 185MPa 205MPa 132MPa 178MPa Bending strength 245MPa 268MPa 165MPa 235MPa interfacial peel strength 68.5N / 25mm 75.2N / 25mm 28.6N / 25mm 62.8N / 25mm Interface solder filling morphology Dense, full and without defects Dense, full and without defects Large areas of unwelded holes The solder filler is dense, but microcracks exist at the interface edges. Analysis of Table 1 shows that the interfacial peel strength of Examples 3 and 4 reached 68.5 N / 25 mm and 75.2 N / 25 mm, respectively, while the interfacial peel strength of Comparative Example 1 was only 28.6 N / 25 mm, a decrease of 58.2% compared with Example 3. Scanning electron microscopy showed that there were large areas of unbonded holes in the brazing layer of Comparative Example 1. The reason for this was that the back of the overall ceramic plate was a planar structure, and the brazing filler metal was not spread evenly during the brazing process. In addition, the difference in thermal expansion coefficients between ceramic and aluminum alloy caused large residual stress at the interface during cooling, resulting in cracking inside the brazing filler metal layer. Examples 3 and 4 employ modular ceramic anchoring units, with each anchoring column independently brazed. The brazing filler metal spreads fully in the annular groove, and the interface brazing filler metal is dense, full, and defect-free, verifying the key role of discrete array assembly and micro-annular groove filling in the interface connection quality. The bending strengths of Examples 3 and 4 reached 245 MPa and 268 MPa, respectively, while the bending strength of Comparative Example 1 was only 165 MPa, a decrease of 32.7% compared to Example 3. The reason for this is that the planar brazed interface of Comparative Example 1 experienced severe stress concentration under bending load, and the cracks propagated rapidly along the interface. In Examples 3 and 4, the dovetail-shaped anchoring columns and the three stepped dovetail annular microgrooves formed a macroscopic tenon-and-mortise interlocking and microscopic mechanical anchoring, and the bending load was effectively transferred to the aluminum alloy lattice substrate through the anchoring columns, significantly improving the interface bending resistance. The interfacial peel strength of Comparative Example 2 was 62.8 N / 25 mm, and the flexural strength was 235 MPa, which were 8.3% and 4.1% lower than those of Example 3, respectively. Scanning electron microscopy showed that the brazing filler metal of Comparative Example 2 was densely filled, but microcracks existed at the interface edge. The reason for this was that Comparative Example 2 lacked a compliant buffer structure, the assembly hole had a rigid hole wall, and the spiral elastic thin-walled beam around the anchor post was missing during the brazing cooling process. The thermal mismatch stress could not be released through the elastic deformation of the thin-walled beam, and the stress concentration in the local area at the interface edge exceeded the strength of the brazing filler metal layer, resulting in microcracks. This verified the important contribution of the compliant buffer structure to stress release and interface integrity.
[0014] Thermal cycling weathering performance test Lightweight high-strength ceramic-aluminum decorative composite panels prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2 were cut into 200mm × 200mm samples. After being placed under standard conditions for 24 hours, the samples were placed in a thermal cycling test chamber. The cycling conditions were: maintaining a temperature of -40℃ for 1 hour, heating to 120℃ at a rate of 5℃ / min and maintaining for 1 hour, and cooling to -40℃ at a rate of 5℃ / min for one cycle. The number of cycles was set to 50. After the test, the samples were removed and allowed to recover under standard conditions for 2 hours. The peel strength after cycling was tested according to GB / T 7122-1996, and the flexural strength after cycling was tested according to GB / T 1447-2005. The peel strength retention rate and flexural strength retention rate were calculated, and the surface condition of the ceramic layer after cycling was visually observed. Each group of samples was tested in parallel three times, and the average value was taken and the test results were recorded. Table 2. Results of thermal cycling weathering performance test Peel strength before cycle / N / 25 mm 68.5 75.2 28.6 62.8 Post-cycle peel strength / N / 25 mm 60.2 68.5 10.2 48.5 Peel strength retention rate / % 87.9 91.1 35.7 77.2 Circulation-prepared bending strength / MPa 245 268 165 235 Cyclic bending strength / MPa 218 248 98 188 Bending strength retention rate / % 89.0 92.5 59.4 80.0 Appearance after 50 hot and cold cycles The ceramic surface is intact and without warping. The ceramic surface is intact and without warping. The edges of the ceramic slab are warped and falling off. Microcracks at the edge of local ceramic units Analysis of Table 2 shows that after 50 thermal cycles, the peel strength retention rates of Examples 3 and 4 reached 87.9% and 91.1%, respectively, and the flexural strength retention rates reached 89.0% and 92.5%, respectively. The ceramic surface layer remained intact without warping, proving that the discrete array design and compliant buffer structure of the modular ceramic anchoring unit work together to enable each ceramic anchoring unit to independently cope with thermal mismatch deformation. The spiral elastic thin-walled beam absorbs thermal stress through elastic deformation, the brazing interface remains intact, and the composite plate has excellent interface durability under extreme temperature alternation environment. The peel strength retention rate and flexural strength retention rate of Example 4 were 3.2 and 3.5 percentage points higher than those of Example 3, respectively. The reason for this is that Example 4 used a higher preheating temperature and a longer holding time, resulting in better overall temperature uniformity of the pre-assembled body. During brazing, the thermal expansion states of the anchor post and the assembly hole were consistent, and the brazing filler metal was filled more fully. At the same time, the gradient cooling rate of Example 4 was slower, and the thermal stress was released more thoroughly. Comparative Example 1 showed a peel strength retention rate of only 35.7% and a flexural strength retention rate of only 59.4%. After 50 thermal cycles, the ceramic plate exhibited edge warping and detachment. The analysis suggests that the difference in thermal expansion coefficients between the overall ceramic plate and the aluminum alloy substrate was approximately 17 × 10⁻⁶. -6 / ℃, under temperature alternation from -40℃ to 120℃, the cumulative plastic strain at the interface far exceeds the withstand limit of the solder layer. The interface debonding starts from the corners and gradually extends towards the center, eventually leading to the partial detachment of the ceramic plate. Comparative Example 2 exhibited a peel strength retention rate of 77.2% and a flexural strength retention rate of 80.0%. After 50 thermal cycles, microcracks appeared at the edges of local ceramic units. The reason for this was that Comparative Example 2 lacked a compliant buffer structure, and the rigid hole wall could not absorb the alternating stress generated by the thermal cycle. During each cycle, the brazing filler metal layer around the anchor post was subjected to alternating tensile and compressive loads, resulting in low-cycle fatigue damage as the number of cycles increased. Microcracks initiated and propagated in the brazing filler metal layer, verifying the key contribution of the compliant buffer structure to thermal cycle durability.
[0015] Impact resistance test Samples of the lightweight, high-strength ceramic-aluminum decorative composite panels prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2 were cut into 150mm × 150mm specimens. After being placed under standard conditions for 24 hours, they were subjected to drop hammer impact tests according to GB / T 14153-1993 "Rigid Plastics - Drop Hammer Impact Test Method". The drop hammer mass was 1kg, the impact height was 500mm, and the impact head diameter was 12.7mm. After the impact, the damage to the ceramic surface layer and the interface debonding were visually observed, and the number of cracks and the debonding area of the ceramic surface layer after the impact were recorded. Each group of samples was tested in parallel three times, and the average value was taken and the test results were recorded. Table 3. Impact resistance test results Number of cracks after impact / lines 1-2 0-1 8-12 2-3 <![CDATA[Debonded area after impact / cm 2 > 3.5 2.2 45.6 8.5 Damage morphology around the impact point Localized cracks in the ceramic unit near the impact point Minor cracks near the impact point Radial large-area cracking and debonding at the impact point 3-5 ceramic units around the impact point loosened Analysis of Table 3 shows that the debonding areas of Examples 3 and 4 after a 1kg drop hammer impact of 500mm were 3.5cm² and 3.5cm², respectively. 2 and 2.2cm 2The impact damage is limited to 1-2 ceramic units near the impact point. The reason is that the discrete array structure of the modular ceramic anchoring unit limits the impact energy to the loaded unit and its adjacent area. The dovetail anchoring column and the compliant buffer structure of the aluminum alloy lattice base absorb the impact energy through the plastic deformation of the thin-walled beam, preventing the damage from propagating to a long distance. The debonding area of Comparative Example 1 is as high as 45.6 cm². 2 Radial cracking and debonding occurred around the impact point. The reason was that the continuous structure of the integral ceramic plate caused the impact stress wave to propagate a long distance along the plate surface. Under the impact energy, the brittle ceramic generated a large number of cracks that penetrated the entire plate, which verified the effectiveness of discrete array assembly in isolating impact damage. The debonding area of Comparative Example 2 is 8.5 cm². 2 Three to five ceramic units around the impact point became loose, and the damage range was between that of Example 3 and Comparative Example 1. The reason for this was that the rigid hole wall could not provide a buffer energy absorption mechanism, and the impact energy was directly transferred to the hole wall interface of the surrounding units through the anchor post, resulting in damage to the interfaces of multiple adjacent units.
[0016] Repairability testing The lightweight, high-strength ceramic-aluminum decorative composite panels prepared in Examples 3, 4, Comparative Example 1, and Comparative Example 2 were cut into 150mm × 150mm samples. After being placed under standard conditions for 24 hours, three locations were randomly selected on each sample for simulated damage treatment. In Examples 3, 4, and Comparative Example 2, the selected ceramic anchoring units were locally heated at 580℃ for 5 minutes using a handheld hot air gun before being removed. In Comparative Example 1, a circular damage area with a diameter of 15mm was created on the surface of the ceramic plate, and ceramic fragments were removed by heating. After damage treatment, active brazing paste was reapplied to the same location, and a new ceramic unit or patch was replaced. The repair was completed by holding the plate at 580℃ for 5 minutes. The interfacial peel strength of the repaired area was tested according to GB / T 7122-1996, the peel strength recovery rate was calculated, and the condition of the ceramic surface layer around the repaired area was visually observed. Three repair points were tested in parallel for each group of samples, the average value was taken, and the test results were recorded. Table 4. Results of Repairability Tests Original peel strength / N / 25 mm 68.5 75.2 28.6 62.8 Peel strength after repair / N / 25 mm 63.2 70.8 12.8 56.5 Peel strength recovery rate / % 92.3 94.1 44.8 90.0 Condition of the surrounding area after repair Adjacent units intact Adjacent units intact Extensive warping around the perimeter Adjacent units are intact, with microcracks at the edges. As shown in Table 4, the peel strength recovery rates after repair in Examples 3 and 4 reached 92.3% and 94.1%, respectively. The adjacent ceramic units around the repair point were intact. The reason for this is that the discrete array design of the modular ceramic anchoring unit allows each unit to be connected independently. Local heating only affects the damaged unit. The heat is blocked by the discrete ceramic unit intervals and will not be conducted to the interface of the adjacent unit. In addition, the dovetail anchoring column and the ring groove structure can form a complete mechanical interlock again after re-brazing, and the repair effect is close to the original state. The recovery rate of Example 4 was 1.8 percentage points higher than that of Example 3. The reason for this is that Example 4 used the ceramic anchoring unit prepared in Example 2, which had a higher sintering density and maintained good secondary capillary spreading and wettability of the brazing filler metal during repair. The peel strength recovery rate of Comparative Example 1 after repair was only 44.8%, and a large area of ceramic plate warping appeared around the repaired area. The reason for this was that the heat was rapidly conducted to the periphery along the brazing layer during local heating repair of the planar brazing structure of the integral ceramic plate, causing the brazing layer in the undamaged area to soften and fail. In addition, there was a seam between the ceramic patch and the original plate, which could not restore the integrity. This verified that the integral ceramic-aluminum composite plate is not repairable. Comparative Example 2 showed a peel strength recovery rate of 90.0% after repair. The adjacent units around the repair point were intact, but microcracks appeared at the edges. The reason for this was that although Comparative Example 2 had replaceable ceramic anchor units, it lacked a compliant buffer structure. The rigid hole wall was subjected to mechanical scraping during removal and insertion, resulting in micro-damage. After repair, there was no spiral elastic thin-walled beam to absorb thermal stress during brazing and cooling, which led to the formation of microcracks at the edges of the repair point. The recovery rate was lower than that of Example 3, which verified the key role of the compliant buffer structure in the release of secondary thermal stress at the interface after repair.
[0017] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A molding method for an interface buffer reinforcement structure of a lightweight, high-strength ceramic-aluminum decorative composite panel, characterized in that, Based on modular ceramic anchoring units, a lightweight, high-strength ceramic-aluminum decorative composite panel with an interface buffering and enhanced structure is obtained through the synergistic effect of discrete array assembly, low-temperature active brazing connection, flexible structural stress buffering and functional gradient interface reinforcement, achieving macroscopic tenon and mortise interlocking, microscopic annular groove filling and controllable interface reaction wetting combination.
2. The molding method for the interface buffer reinforcement structure of a lightweight high-strength ceramic-aluminum decorative composite panel according to claim 1, characterized in that, The modular ceramic anchoring unit is composed of the following components by weight percentage: 82.5% alumina powder, 5% yttrium-stabilized zirconia powder, 3.5% polyvinyl butyral, 2% dibutyl phthalate, 1.5% stearic acid, 1.2% magnesium oxide, 0.8% titanium dioxide, 0.5% oleic acid, 0.5% polyethylene glycol 400, 0.3% nano-graphite powder, 0.2% silicon carbide whiskers, 0.5% low-melting-point glass powder, and 1.5% anhydrous ethanol.
3. The molding method for the interface buffer reinforcement structure of a lightweight high-strength ceramic-aluminum decorative composite panel according to claim 1, characterized in that, The method for preparing the modular ceramic anchoring unit includes the following steps: A1: Place alumina powder in a vacuum drying oven, set the temperature to 120-140℃, and the vacuum degree to -0.08 to -0.10MPa, and dry for 12-16 hours to obtain dried alumina powder. Place yttrium-stabilized zirconia powder in a vacuum drying oven, set the temperature to 100-120℃, and the vacuum degree to -0.08 to -0.10MPa, and dry for 10-14 hours to obtain dried yttrium-stabilized zirconia powder. Place magnesium oxide, titanium dioxide, and silicon carbide whiskers in vacuum drying ovens, set the temperature to 100-120℃, and the vacuum degree to -0.08 to -0.10MPa, and dry for 8-12 hours to obtain dried magnesium oxide, dried titanium dioxide, and dried silicon carbide whiskers. A2: Add dry alumina powder, dry yttrium-stabilized zirconium oxide powder, dry magnesium oxide, dry titanium dioxide, dry silicon carbide whiskers and stearic acid into a ball mill, use anhydrous ethanol as the ball milling medium, set the ball milling speed to 300-400 rpm, the ball milling time to 4-6 h, and the ball-to-material ratio to 3:
1. After ball milling, transfer the powder to an oven and dry it at 80-100℃ for 6-8 h. Then pass it through a 200-mesh sieve to obtain the pretreated ceramic mixed powder. A3: Place polyvinyl butyral in a vacuum drying oven, set the temperature to 60-80℃, and the vacuum degree to -0.08 to -0.10MPa, and dry for 6-10 hours to obtain dried polyvinyl butyral. Place polyethylene glycol 400 in a vacuum drying oven, set the temperature to 80-100℃, and the vacuum degree to -0.08 to -0.10MPa, and dry for 4-8 hours to obtain dried polyethylene glycol 400. A4: Add the pretreated ceramic mixed powder, dried polyvinyl butyral, dibutyl phthalate, oleic acid, dried polyethylene glycol 400, nano-graphite powder and low melting point glass powder to a mixer for mixing. Set the mixing temperature to 150-170℃, the mixing speed to 30-50 rpm, and the mixing time to 30-60 min. After mixing, crush the material and pass it through a 10-mesh sieve to obtain the injection molding feed. A5: Add the injection molding feedstock into the injection molding machine, set the injection temperature to 160-180℃, the injection pressure to 80-100MPa, and the injection speed to 15-25cm. 3 / s, holding pressure is 60-80MPa, holding time is 5-10s, mold temperature is 40-60℃, injection molding yields a ceramic blank with a decorative surface on the upper surface and an integrally formed dovetail-shaped anchor column in the center of the lower surface. The anchor column body is engraved with 3 stepped dovetail annular microgrooves, and the cross-sectional dimension of the cantilever end of the anchor column is larger than the cross-sectional dimension of the root. A6: Place the ceramic green body in a degreasing furnace and heat it from room temperature to 300-350℃ at a heating rate of 0.5-1℃ / min. Hold it at 300-350℃ for 2-3 hours for low-temperature degreasing. Then heat it to 550-600℃ at a heating rate of 1.5-2.5℃ / min and hold it at 550-600℃ for 3-5 hours for medium-temperature degreasing. Flowing nitrogen gas is introduced throughout the degreasing process at a flow rate of 2-4L / min. After degreasing, a degreased ceramic green body is obtained. A7: The degreased ceramic green body is fed into a high-temperature sintering furnace and heated to 1100-1300℃ at a heating rate of 3-6℃ / min. It is then held at 1100-1300℃ for 1-2 hours for pre-sintering. Next, it is heated to 1620-1680℃ at a heating rate of 5-10℃ / min and held at 1620-1680℃ for 2-4 hours for densification sintering. Flowing argon gas is introduced throughout the sintering process at a flow rate of 1-3L / min. After sintering, the temperature is lowered to 800℃ at a cooling rate of 5-10℃ / min and held at 800℃ for 1-2 hours. After holding, it is cooled to room temperature with the furnace. Then, the anchoring column part of the ceramic anchoring unit is precision ground. After grinding, the dimensional tolerance of the anchoring column is controlled within ±0.015mm, and the surface roughness Ra≤0.8um, thus obtaining the modular ceramic anchoring unit.
4. The molding method for the interface buffer reinforcement structure of a lightweight, high-strength ceramic-aluminum decorative composite panel according to claim 1, characterized in that, Includes the following steps: S1: Select 6061 aluminum alloy powder, with a feeding amount of 8-15 kg. Place the aluminum alloy powder in a vacuum drying oven, set the temperature to 100-120℃, the vacuum degree to -0.06 to -0.08 MPa, and the drying time to 8-12 h to obtain dried aluminum alloy powder. Load the dried aluminum alloy powder into the powder supply cylinder of the selective laser melting equipment. Import the three-dimensional model of the aluminum alloy lattice substrate into the control system of the equipment, set the laser power to 200-300W, the scanning speed to 800-1200 mm / s, the powder layer thickness to 30-50 μm, the spot diameter to 60-100 μm, the scanning spacing to 80-120 μm, the substrate preheating temperature to 150-200℃, and the oxygen content in the cavity to below 100 ppm. Use a strip scanning strategy to melt and form the aluminum alloy lattice substrate layer by layer. S2: The aluminum alloy lattice substrate is separated from the substrate by wire cutting and placed in a vacuum heat treatment furnace for stress-relief annealing. The annealing temperature is set at 280-320℃ and the annealing holding time is 2-4h. After annealing, the substrate is cooled to below 100℃ in the furnace and then air-cooled to room temperature to obtain the stress-relief aluminum alloy lattice substrate. The stress-relief aluminum alloy lattice substrate is then subjected to solution aging heat treatment. The solution temperature is set at 520-540℃ and the solution holding time is 1-2h. After solution treatment, the substrate is immediately water-quenched at a water temperature of 25-35℃. After water quenching, the substrate is transferred to an aging furnace. The aging temperature is set at 155-175℃ and the aging holding time is 6-10h. After aging, the substrate is air-cooled to room temperature to obtain the heat-treated aluminum alloy lattice substrate. S3: Arrange the modular ceramic anchoring units according to the designed array and insert them one by one into the corresponding holes of the aluminum alloy lattice substrate. The number of ceramic anchoring units inserted is 200-280 per square meter. Use assembly positioning fixtures to ensure that the upper surfaces of each ceramic unit are coplanar and that the dovetail anchoring posts are completely suspended inside the aluminum alloy lattice substrate. The cantilever gap between the end face of the anchoring post and the bottom surface of the assembly hole of the lattice substrate is 1-2mm, resulting in a pre-assembled ceramic surface lattice substrate. After assembly, place the ceramic surface lattice substrate... The pre-assembled assembly is placed on the inspection table and inspected under an inspection light source with an illuminance of 1200 lx to check the neatness of the ceramic unit arrangement and the insertion depth of the anchor column. It is confirmed that there are no misalignments or missing insertion defects. The ceramic surface lattice substrate pre-assembled assembly is placed in a preheating furnace and preheated as a whole in an air atmosphere or protective atmosphere. The preheating temperature is set to 380-420℃, the heating rate is 3-6℃ / min, and the holding time is 20-40min to make the overall temperature of the pre-assembled assembly uniform, thus obtaining the preheated pre-assembled assembly. S4: Transfer the preheated pre-assembled body to the connecting fixture, which has a heat preservation function and a fixture temperature of 380-420℃. Apply a quantitative amount of active brazing filler paste to the annular gap between the root of each anchor post and the opening of the assembly hole. The amount of brazing filler paste required for each ceramic anchor unit is 30-60g. Set the heating temperature of the connecting fixture to 580-610℃ to melt the active brazing filler paste. Apply an auxiliary pressure of 0.1-0.3MPa and hold at 580-610℃ for 5-10 minutes to complete the interface connection. S5: After completing the interface connection, remove the composite plate from the connection fixture and immediately transfer it into a homogenizing furnace. Hold it at 550-580℃ for 1-2 hours to release high-temperature stress. Then, cool it using a gradient temperature control method. Set the first cooling stage to cool from 550-580℃ to 300-320℃ at a rate of 1-2℃ / min, the second cooling stage to cool from 300-320℃ to 150-180℃ at a rate of 5-8℃ / min, and the third cooling stage to cool naturally from 150-180℃ to room temperature with the furnace. After cooling, the interface-bonded ceramic-aluminum composite plate is obtained. S6: The interface-bonded ceramic-aluminum composite panel is sent to the grinding and polishing station. Diamond grinding fluid is used to grind and polish the ceramic surface layer step by step. The coarse grinding wheel mesh size is set to 180-320 mesh, and the coarse grinding feed is 0.05-0.1mm. The semi-fine grinding wheel mesh size is set to 600-800 mesh, and the semi-fine grinding feed is 0.02-0.05mm. The fine grinding wheel mesh size is set to 1500-2000 mesh, and the fine grinding feed is 0.01-0.02mm. The polishing cloth wheel speed is 1200-1800rpm, the polishing fluid particle size is 0.5-1.5um, and the polishing time is 5-15min. After polishing, the composite panel is placed on the inspection table and the surface roughness and gloss of the ceramic surface layer are checked under an inspection light source with an illuminance of 1200lx. It is confirmed that there are no scratches or pit defects, and a lightweight, high-strength ceramic-aluminum decorative composite panel with an interface buffer reinforcement structure is obtained.
5. The molding method for the interface buffer reinforcement structure of a lightweight high-strength ceramic-aluminum decorative composite panel according to claim 2, characterized in that, The alumina powder has an average particle size of 0.8 μm, and the magnesium oxide has an average particle size of 0.2 μm.
6. The molding method for the interface buffer reinforcement structure of a lightweight, high-strength ceramic-aluminum decorative composite panel according to claim 2, characterized in that, The yttrium oxide stabilized zirconia powder has a yttrium oxide molar content of 3% and an average particle size of 0.5 μm.
7. The molding method for the interface buffer reinforcement structure of a lightweight, high-strength ceramic-aluminum decorative composite panel according to claim 2, characterized in that, The silicon carbide whiskers have a diameter of 0.8 μm, a length of 20 μm, and an aspect ratio of 25.
8. The molding method for the interface buffer reinforcement structure of a lightweight, high-strength ceramic-aluminum decorative composite panel according to claim 2, characterized in that, The low-melting-point glass powder is bismuth borosilicate glass powder, with a softening point of 485℃ and an average particle size of 0.8μm.
9. The molding method for the interface buffer reinforcement structure of a lightweight, high-strength ceramic-aluminum decorative composite panel according to claim 4, characterized in that, In the three-dimensional model of the aluminum alloy lattice substrate described in step S1, a compliant buffer structure is designed at the position corresponding to the assembly hole of each ceramic anchoring unit. The compliant buffer structure consists of three spiral elastic thin-walled beams distributed in a ring around the assembly hole. The thickness of the thin-walled beam is 0.5 mm, the length is 3 mm, and the spiral angle is 90°.
10. The molding method for the interface buffer reinforcement structure of a lightweight, high-strength ceramic-aluminum decorative composite panel according to claim 4, characterized in that, The active solder paste described in step S4 is composed of Al-Si eutectic alloy powder, Mg powder, potassium fluoroaluminate flux, and ethyl cellulose. The Si content in the Al-Si eutectic alloy powder is 12%, and the mass ratio of Al-Si eutectic alloy powder, Mg powder, potassium fluoroaluminate flux, and ethyl cellulose is 88:2:8:2.